Accelerated Partial Breast Irradiation: Using the CyberKnife as the Radiation Delivery Platform in the Treatment of Early Breast Cancer - Vermeulen, Sandra; Cotrutz, Cristian; Buchanan, Claire; Dawson, Patricia; Morris, Astrid; Porter, Bruce; Meier, Robert (Frontiers in Oncology, 2011)
We evaluate the CyberKnife (Accuray, Incorporated, Sunnyvale, CA) for non-invasive delivery of accelerated partial breast irradiation (APBI) in early breast cancer patients. Between 6/2009 and 5/2011, 9 patients were treated with CyberKnife APBI. Normal tissue constraints were imposed as outlined in the National Surgical Adjuvant Breast and Bowel Project B-39/Radiation Therapy Oncology Group 0413 (NSABP/RTOG) Protocol (Vicini and White, 2007). Patients received a total dose of 30 Gy in 5 fractions (group 1, n=2) or 34 Gy in 10 fractions (group 2, n=7) delivered to the planning treatment volume (PTV) defined as the clinical target volume (CTV) + 2 mm. The CTV was defined as either the lumpectomy cavity plus 10 mm (n=2) or 15 mm (n=7). The cavity was defined by a T2-weighted non-contrast breast MRI fused to a planning non-contrast thoracic CT. The CyberKnife Synchrony system tracked gold fiducials sutured into the cavity wall during lumpectomy. Treatments started 4-5 weeks after lumpectomy. The mean PTV was 100 cm3 (range, 92-108 cm3) and 105 cm3 (range, 49-241 cm3) and the mean PTV isodose prescription line was 70% for groups 1 and 2, respectively. The mean percent of whole breast reference volume receiving 100% and 50% of the dose (V100 and V50) for group 1 was 11% (range, 8-13%) and 23% (range, 16-30%) and for group 2 was 11% (range, 7-14%) and 26% (range, 21- 35.0%) , respectively. At a median 7 months follow-up (range, 4-26 months), no acute toxicities were seen. Acute cosmetic outcomes were excellent or good in all patients; for those patients with more than 12 months follow-up the late cosmesis outcomes were excellent or good. In conclusion, the lack of observable acute side effects and current excellent/good cosmetic outcomes is promising. We believe this suggests the CyberKnife is a suitable non-invasive radiation platform for delivering APBI with achievable normal tissue constraints.